Picture Book Series as A Medium to Foster Reading Interest of Madrasah Ibtidaiyah Children - Khikmah, Nur; Ningsih, Tutuk (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Indonesian people's reading interest, especially for MI/SD children, is still relatively low because they prefer playing online games, watching television, etc. This factor causes their reading ability is still lacking. In addition, there are reading books (both story books and textbooks) in school institutions which are still monotonous with colorless pictures so that children get bored easily and are not interested in reading them. Based on the phenomenon above, the teacher's interest in reading in MI/SD children must be increased because